REVIEW OF THE FIRST YEAR OF HUMANITARIAN RESPONSE IN UKRAINE AFTER RUSSIAN INVASION: MULTIPURPOSE CASH ASSISTANCE LENS - Klymenko, Tatiana (Collection of scientific papers «ΛΌГOΣ», 2023)
The humanitarian response in Ukraine, within the framework of global international assistance to the population of Ukraine suffering from Russian military aggression, began immediately after the invasion on February 24, 2022: the first reactions of the organizations present were received immediately, others began to unfold their programs as they formed. In mid-2023, more than 100 humanitarian organizations are actively operating in Ukraine.